Pharmacovigilance in Clinical Trails - Shelke Nikita; Shelke Harshal B; Sathe Dipti B; Sangale Vaibhavi S. (Asian Journal of Pharmaceutical Research and Development, 2026)
An essential component of the entire drug development process is pharm acovigilance. Pharmacovigilance is the ongoing observation, assessment, and interpretation of possible side effects or other problems pertaining to medications. By weighing the advantages and disadvantages of particular medications, this promotes patient safety. Pharmacovigilance has been more effective with the use of information technology, allowing for improved monitoring and clinical safety procedures. It is essential to ensuring the cost-effectiveness, safety, and efficacy of medications over their entire lifecycle, from research to postmarketing monitoring. ICH GCP, USFDA standards, and other regulatory g uidelines regulate the clinical trial procedure.The evidence underpinning for regulatory judgments about safe and effective medications is provided by clinical studies. A crucial part of every stage of the drug development life cycle is safety evaluation A crucial part of every stage of the drug development life cycle is safety evaluation. The ultimate objective of pharmacovigilance in clinical trials is to monitor and evaluate the test product's safety profile.